Digital Comics as an Innovative Media in Mahārah qirā’ah Learning: A Literature Review: Komik Digital sebagai Media Inovatif dalam Pembelajaran Keterampilan Membaca (Mahārah Qirā’ah): Tinjauan Literatur - Aldereza Lidiya Mazyuna; Asep Sopian (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
Learning Mahārah qirā’ah (reading skills) in Arabic still faces various obstacles, mainly because the approach used is often monotonous, textual, and less interactive. This has an impact on low motivation and student engagement, especially in the current digital era. This research aims to examine the use of digital comics as an innovative medium for learning Mahārah Qira'ah and to explore their effectiveness, challenges, and opportunities for implementation in Indonesian schools. This study employed a Systematic Literature Review (SLR) approach that involved an initial screening of 90 articles, which were subsequently assessed using predefined inclusion–exclusion criteria and quality appraisal, resulting in 15 final studies deemed relevant for in-depth analysis. The results of the study show that digital comics are effective in presenting Arabic reading texts visually, narratively, and contextually. This media increases student attractiveness, strengthens understanding of sentence structure, and facilitates mastery of tajweed and pronunciation. Various forms of digital comics, such as flipbooks, webtoons, and Canva, have consistently been shown to increase motivation and learning outcomes. However, challenges remain, including limited infrastructure, insufficient teacher training, and a lack of curriculum-aligned content that reflects local context. Therefore, digital comics are feasible as an effective alternative learning medium when designed interactively and contextually. This study recommends teacher training, local content development, and the integration of comics in project-based learning and e-learning. Keywords: Digital Comics, Innovative Media, Maharah Qira'ah